Pemanfaatan Forms sebagai Media Pembelajaran Remedial di SMPN 230 Jakarta - Sukmawati, Sukmawati (Jurnal Didaktika Pendidikan Dasar, 2018)
The use of forms as media was aimed at assisting teachers with limited face-to-face interaction in remedial learning, especially whose minimum performance indicators were not achieved.  The current research implemented an experimental design using two forms, they are, forms-without-comment and forms-with-comments. The students chose the remedial media themselves. They were also asked to complete a survey sheet to know their ideas about the remedial learning. Data analysis indicate that the forms-with-comments resulted in better achievement than the forms-without-comment. The pupils’ performance indicator was achieved as much as 88%. The pupils’ satisfaction level achieved was as much as 88% on the remedial learning program. The pupils’ comprehension in writing texts improved to 96%. In conclusion, the use of forms-with-comments could assist teachers with limited face-to-face interaction in remedial learning and improving the pupils’ achievement of the minimum performance indicator.